Optimization of Parameters for a Scraping-Rotating-Brushing Dehilling Machine Using EDEM - Yang, Shu-Ming; Cui, Zheng; Wang, Qian; Gao, De-Hua; Li, Mao-Qiang; Wang, Yu-Tan; Li, Jin-Hai (International Journal of Agricultural and Biological Engineering, 2024)
The eastern foot of Helan Mountain in the Ningxia Hui Autonomous Region stands out as one of the prime grape-growing regions in China. Owing to the region's dry, cold and windy winter climate, it is common practice to cover grapevines with soil and form ridges for winter protection. These soil ridges are then cleared in the following spring to allow grapevines to grow unhindered. However, the conventional dehilling machines have often exhibited a low soil clearing rate, leaving a substantial amount of residual soil behind. This inefficiency soil cleaning operations cause a high labor intensity in subsequent manual soil removal process. To address this challenge, we designed a scraping-rotating-brushing dehilling machine. In this paper, we utilized the Discrete Element Method (DEM) to determine the optimal structural parameters for the critical components, including the scraper, rotary blade, and flexible brush. We constructed DEM models for the single scraper, scraper-rotary blade, and scraper-rotary blade-brush, enabling simulations of their respective working processes. Through simulation analysis, we obtained the optimal combination parameters of the physical prototype. To verify the accuracy of the simulation, we conducted field experiments to measure the clearing rate of the scraping-rotating-brushing dehilling machine. The results demonstrated an extremely low relative error of just 0.05% between the DEM simulation results and the outcomes of the field tests, thereby confirming the accuracy of our DEM model. The success of the DEM model implementation highlights its potential in the design and development of grape soil cleaning machinery. This innovative approach not only reduces the cost associated with prototype development but also provides reference for the research and development of other related agricultural machinery.